Attitudes of the Elderly towards Interprofessional Cooperation and Collaborative Pharmacy Practices: Questionnaire development - Ilić, Velibor; Tasić, Ljiljana; Marinković, Valentina (Archives of Pharmacy, 2021)
Population aging is progressing at the highest rate historically, leading to an increased morbidity. Therefore, higher levels of collaborative pharmaceutical practice (CPP) and interprofessional collaboration (IPC) are expected to provide the necessary improvement to the healthcare system performance. For a strong body of literature to be built in the area of CPP and IPC, methodologically sound research studies must be completed, using questionnaires with well-developed psychometric properties. Therefore, the objective was to develop a questionnaire aimed at researching the attitudes of the elderly (65+) towards IPC and CPP. A structured questionnaire was developed using the Delphi method by a team of experts (n=8) within four rounds of meetings. Reliability, question correlation and factor analysis were used for questionnaire validation. Questionnaire validation (n=40) determined the Cronbach’s Alpha to be at the high value of 0.774, and reliability analysis of questionnaire’s scales on the total sample (n=185) in the five Geriatric Centers confirmed a relatively high value of 0.736. Interclass correlation coefficient values were highly significant (ICC=0.749; p
Keywords: Questionnaire development; collaborative practice; attitudes of the elderly; Delphi method